Jacques Parizeau : un économiste dans la cité - Jean-Philippe Carlos (Revue Interventions Économiques)
This article focuses on the first phase of the intellectual trajectory of the economist Jacques Parizeau (1930-2015), from his entry into office as a professor at the École des Hautes Études Commerciales de Montréal (1955) to his beginnings as a consultant within the Quebec state apparatus (1961-62). We analyze its anchoring in the historical institutional mission of the HEC, launched by characters such as Édouard Montpetit, Esdras Minville and François-Albert Angers, as well as its economic thought, rooted in Keynesian and nationalist schemes. In following Parizeau’s trajectory, we highlight some of the mechanisms that led to the creation of a Francophone economic technocracy within the Quebec state apparatus in the 1960s.